Simultaneous profiling of optically smooth and rough surfaces using dual-wavelength interferometry - Upputuri, Paul Kumar (2021)
Interferometers are widely used in industry for surface profiling of microsystems. It can be used to inspect both smooth (reflective) and rough (scattering) surfaces in wide range of sizes. If the object surface is smooth, the interference between reference and object beam results in visible fringes. If the object surface is optically rough, the interference between reference and object beam results in speckles. Typical microsystems such as MEMS consist of both smooth and rough surfaces on a single platform. Recovering the surface profile of such samples with single-wavelength is not straight forward. In this paper, we will discuss a dual-wavelength approach to measure surface profile of both smooth and rough surfaces simultaneously. Interference fringe pattern generated on a combined surface is acquired at two different wavelengths. The wrapped phases at each wavelength are calculated and subtracted to generate contour phase map. This subtraction reveals the contour fringes of rough and smooth surfaces simultaneously. The dual-wavelength contour measurement procedure and experimental results will be presented.